Allium sativum (garlic extract) as a green corrosion inhibitor with biocidal properties for the control of MIC in carbon steel and stainless steel in oilfield environments - Parthipan, P.; Elumalai, P.; Narenkumar, J.; Machuca Suarez, Laura; Murugan, K.; Karthikeyan, O.; Rajasekar, A. (2018)
© 2018 Elsevier Ltd In the present study, the effectiveness of garlic extract to inhibit the bio-corrosion of carbon steel API 5LX (CS) and stainless steel 316 (SS) in the presence of Bacillus subtilis A1 and Streptomyces parvus B7 was estimated. The antibacterial activity of the garlic extract (GAE) was tested; 100 ppm of the GAE was identified as the minimal inhibitory concentration for bacterial growth. Weight loss and electrochemical studies including linear polarization and AC impedance along with surface analysis were used to examine the corrosion inhibition efficiency (IE) for both metals in the presence of GAE. The strains A1, B7 and their mixed consortium caused severe corrosion to both metals. In the presence of GAE the IE for abiotic system was about 81 ± 3% and 75 ± 3%, while in the presence of the mixed consortium the IE was 72 ± 3% and 69 ± 3% for CS and SS, respectively. Gas chromatography mass spectrum analysis of GAE indicated that GAE contains a sulphur rich compound which plays a key role in the inhibition of both bacterial development and corrosion. This is the first time garlic extract is proposed as a green corrosion inhibitor with biocidal activity to control biocorrosion in hypersaline corrosive environment containing microorganisms.